Sensitive, Accurate and Selective Determination of Cd(II) Using Anodic Stripping Voltammetry With In-situ Hg-Bi Film Modified Pencil Graphite Electrode After Magnetic Dispersive Solid Phase Microextraction - Yaman, Burcu; Zaman, Buse Tugba; Bakirdere, Sezgin; Dilgin, Yusuf (WILEY-V C H VERLAG GMBH, 2021)
This paper describes a novel approach to detect Cd(II) using the combination of the differential pulse anodic stripping voltammetry and magnetic nanoparticle based dispersive solid phase microextraction as an efficient, green and accurate method. Currents of Cd(II) increased linearly in the range from 75 to 2000 ngL(-1) Cd(II) with a detection limit of 21.6 ngL(-1). The RSD values of 2.6 and 6.0 % for 1.00 and 0.10 mu g L-1 respectively showed that proposed method has an acceptable repeatability. Recovery values between 92.3 and 98.6 % showed that this approach can be successfully used for determination of Cd(II) in water samples.
Keywords: Cadmium; dispersive solid phase microextraction; stripping voltammetry; magnetic nanoparticles; graphite pencil electrode; EXTRACTION; Chemistry; Electrochemistry